Perceptions of patients with rheumatic diseases on the impact on daily life and satisfaction with their medications: RHEU-LIFE, a survey to patients treated with subcutaneous biological products - González CM; Carmona L; de Toro J; Batlle-Gualda E; Torralba AI; Arteaga MJ; Cea-Calvo L (Patient Preference and Adherence, 2017)
Carlos M González,1 Loreto Carmona,2 Javier de Toro,3 Enrique Batlle-Gualda,4 Antonio I Torralba,5 María J Arteaga,6 Luis Cea-Calvo6 1Department of Rheumatology, Gregorio Marañón Hospital, 2Instituto de Salud Musculoesquelética, Madrid, 3Department of Rheumatology, Hospital Universitario A Coruña, A Coruña, 4Department of Rheumatology, Hospital Universitario de Sant Joan d’Alacant, Alicante, 5Coordinadora Nacional de Artritis, 6Medical Affairs Department, Merck Sharp & Dohme, Madrid, Spain Objective: The aim of this study was to explore perceptions of patients with rheumatic diseases treated with subcutaneous (SC) biological drugs on the impact on daily life and satisfaction with current therapy, including preferred attributes. Methods: A survey was developed ad hoc by four rheumatologists and three patients, including Likert questions on the impact of disease and treatment on daily life and preferred attributes of treatment. Rheumatologists from 50 participating centers were instructed to handout the survey to 20 consecutive patients with rheumatoid arthritis (RA), axial spondyloarthritis (ax-SpA), or psoriatic arthritis (PsA) receiving SC biological drugs. Patients responded to the survey at home and sent it to a central facility by prepaid mail. Results: A total of 592 patients returned the survey (response rate: 59.2%), 51.4% of whom had RA, 23.8% had ax-SpA, and 19.6% had PsA. Patients reported moderate-to-severe impact of their disease on their quality of life (QoL) (51.9%), work/daily activities (49.2%), emotional well-being (41.0%), personal relationships (26.0%), and close relatives’ life (32.3%); 30%–50% patients reported seldom/never being inquired about these aspects by their rheumatologists. Treatment attributes ranked as most important were the normalization of QoL (43.6%) and the relief from symptoms (35.2%). The satisfaction with their current antirheumatic therapy was high (>80% were “satisfied” or “very satisfied”), despite moderate/severe impact of disease. Conclusion: Patients with rheumatic diseases on SC biological therapy perceive a high disease impact on different aspects of daily life, despite being highly satisfied with their treatment; the perception is that physicians do not frequently address personal problems. Normalization of QoL is the most important attribute of therapies to patients. Keywords: rheumatic diseases, quality of life, emotional well-being, biological drugs, patient’s satisfaction